The Impact of Self-efficacy on International Student Entrepreneur Intention - Oladapo Rasul; Festus Victor Bekun; Seyi Saint Akadiri (International Review of Management and Marketing, 2017)
Entrepreneur self-efficacy is the level to which people perception of their capacities to successfully perform the various roles and tasks of entrepreneurship (Chen et al., 1998; De Noble et al., 1999, Foleide, 2011). The research sampled students from two universities in Cyprus. The data was collected through a questionnaire. Statistical Package for Social Science software was used for data analysis. It was discovered that, in exception of motive toward business success and status in the society, emerging small and medium size enterprise do not have motive for economic growth, though the significant relationship between status in the society and self-efficacy were discussed. Conclusively, there exist a negative relationship between self-efficacy and desire for status among entrepreneurs.